Epidemiological survey and molecular characterization of Echinococcus granulosus in cattle in an endemic area of eastern Turkey - Simsek, Sami; Balkaya, Ibrahim; Koroglu, Ergun (Elsevier, 2010)
Cystic echinococcosis (CE) is a zoonotic disease affecting mainly various species of livestock and humans. A survey of cystic echinococcosis in cattle was conducted from December 2008 to April 2009 in an endemic area of eastern Turkey. A total of 1758 cattle were examined and hydatid cysts were found in 33.9% of the cattle (595/1758). Most of the cattle (75.8%) had hydatid cysts only in the lungs, 10.9% only in the liver, 12.4% in the both liver and lungs, 0.7% in the spleen and 0.2% in the heart. 220 of these cysts were examined by PCR of 12S rRNA gene and sequencing of mt-CO1 gene. 147 of 220 cattle isolates showed the same band pattern with 12S rRNA analyses and were identified as G1-G3 complex (Echinococcus granulosus sensu stricto) and also 28 of these were confirmed by mitochondrial CO1 sequencing as Cl genotype. The other 73 samples that did not amplified with 12S rRNA gene specific primers were analyzed for mt-CO1 gene and only 7 samples yielded 446 bp product and after the CO1 sequencing these were identified as G3 genotype. This study confirms the predominance of the sheep strain (G1 genotype) in Turkey and this is the most comprehensive genetic survey of cattle CE in Turkey. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Echinococcus granulosus; Cattle; PCR; Genotype; Turkey